Solution-based Ag-doped ZnSe thin films with tunable electrical and optical properties. Issue 38 (10th September 2015) - Xi, Yang; Bouanani, Lidia El; Xu, Zhe; Quevedo-Lopez, Manuel A.; Minary-Jolandan, Majid
Abstract : Thin film transistors fabricated using ZnSe thin films synthesized using chemical bath deposition. Abstract : We demonstrate a solution-processed large-area method to fabricate intrinsic and silver (Ag)-doped ZnSe thin films with tunable electrical and optical properties. The resulting films were extensively characterized and incorporated as the active layer for TFTs (thin film transistors) and as the buffer layer in solar cells. The effect of Ag-doping on the transport characteristics of the Ag-doped ZnSe films is also discussed.